A Nucleolar Stress–Specific p53–miR-101 Molecular Circuit Functions as an Intrinsic Tumor-Suppressor Network - Fujiwara, Yuko (EBioMedicine, 2018)
BACKGROUND: Activation of intrinsic p53 tumor-suppressor (TS) pathways is an important principle underlying cancer chemotherapy. It is necessary to elucidate the precise regulatory mechanisms of these networks to create new treatment strategies. METHODS: Comprehensive analyses were carried out by microarray. Expression of miR-101 was analyzed by clinical samples of lung adenocarcinomas. FINDINGS: We discovered a functional link between p53 and miR-101, which form a molecular circuit in response to nucleolar stress. Inhibition of RNA polymerase I (Pol I) transcription resulted in the post-transcriptional activation of miR-101 in a p53-dependent manner. miR-101 induced G2 phase–specific feedback regulation of p53 through direct repression of its target, EG5, resulting in elevated phosphorylation of ATM. In lung cancer patients, low expression of miR-101 was associated with significantly poorer prognosis exclusively in p53 WT cases. miR-101 sensitized cancer cells to Pol I transcription inhibitors and strongly repressed xenograft growth in mice. Interestingly, the most downstream targets of this circuit included the inhibitor of apoptosis proteins (IAPs). Repression of cIAP1 by a selective inhibitor, birinapant, promoted activation of the apoptosis induced by Pol I transcription inhibitor in p53 WT cancer cells. INTERPRETATION: Our findings indicate that the p53–miR-101 circuit is a component of an intrinsic TS network formed by nucleolar stress, and that mimicking activation of this circuit represents a promising strategy for cancer therapy. FUND: National Institute of Biomedical Innovation, Ministry of Education, Culture, Sports & Technology of Japan, Japan Agency for Medical Research and Development.